Policy Implementation Model of Tourism Village Development Policy in Cikolelet Tourism Village, Serang Regency - Rahmawati, Rahmawati; Kusuma, Sintya (ANTASENA: Governance and Innovation Journal, 2025)
Policy implementation is a critical process in realizing the objectives of public policy. This study examines the implementation of tourism village development policy in Cikolelet Village, which is based on Village Regulation No. 5 of 2017. Although the policy has been implemented optimally, the development of the tourism village has stagnated. Identified issues include declining tourist visits, limited accessibility and connectivity, and weak promotion and marketing of village-owned tourism assets. The research aims to explore the causes of stagnation using O. Jones’s policy implementation theory, which includes organizational, interpretive, and application dimensions. A qualitative descriptive method was used, involving key informants such as village government officials, leaders and secretaries of the tourism awareness group (Pokdarwis), BUMDes leaders, and local community members. The results indicate that the organizational aspect is functioning well, evidenced by the establishment of Pokdarwis and BUMDes institutions. However, major obstacles include lack of synergy among stakeholders and limited human resource capacity and capability. Moreover, local managers and residents are still unfamiliar with core tourism principles like Sapta Pesona and the tourism village concept. This study recommends the necessity of a pentahelix collaboration model (government, private sector, academia, community, and media) to overcome challenges and revitalize the development of Cikolelet Tourism Village as a leading destination in Serang Regency.